PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE FLASH PROFESIONAL CS6 UNTUK KELAS V MATA PELAJARAN IPA MATERI PESAWAT SEDERHANA - Kusumaningrum, Ananda; Fajriyah, Khusnul; Royana, Ibnu Fatkhu (KALAM CENDEKIA PGSD KEBUMEN, 2018)
ABSTRACT Student concentration and learning interest are only at the beginning of learning. This is due to the lack of use of learning media, teachers have difficulty in choosing learning media and the availability of learning media in schools. Teachers need to use interesting learning media in learning, one solution to using Adobe Flash Professional-based interactive learning media CS6. Research has been done on the validity and practicality of Adobe Flash Professional-based interactive learning media CS6. This research was carried out in three elementary schools, namely SDN 3 Gubug, SDN 1 Kuwaron, and SDN 4 Kuwaron. The validity of the media was obtained from the results of expert validation consisting of three media experts and three material experts. The results obtained from. The average results obtained from three media experts amounted to 88.8% and material experts amounted to 93.78%. The results of the reliability of the three media experts and material experts were 96.4% and 99%. The average of the students' questionnaire responses was at 97.9 and the teacher's response was 98,07%. Based on the data analysis, it shows that the Adobe Flash Professional cs6-based interactive learning media can be said to be valid and practical to be used in science subjects in simple airplane class V elementary school material.Keywords: Development, Interactive Learning Media, Adobe Flash Professional CS6.